Two Decades of Neptune Theatre - Perkyns, Richard (Theatre Research in Canada / Recherches théâtrales au Canada, 1985)
This article traces the changing fortunes of the Neptune Theatre, Halifax, Nova Scotia, under five artistic directors between its beginnings in 1963 and 1983. Cet article suit les fortunes changeantes du Neptune Theatre, Halifax, Nova Scotia, pendant les résidences des cinq metteurs en scène de 1963 a 1983.